PEMBINAAN NARAPIDANA PENGEDAR NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS IIA MATARAM - GUSTI AYU RATIH DAMAYANTI; B. FARHANA KURNIA LESTARI; WA’ID KHAIRUL ABADI (GANEC SWARA, 2023)
This study aims to determine the form of coaching and to analyze the obstacles in fostering narcotics dealer convicts in the Class IIA Mataram Penitentiary so as to find out the efforts to overcome these obstacles. The type of legal research used in this research is empirical legal research. This research is descriptive in nature, data collection was carried out by interviewing convicts of narcotics dealers and correctional officers as samples determined by the author's will or purposive sampling. The author also conducts literature studies and observations/observations on coaching activities. Processing and data analysis is done by qualitative data analysis.Forms of coaching consist of personality coaching and independence coaching. The author also conducts an analysis of internal and external constraints in coaching and knows the efforts to overcome these obstacles. Internal obstacles include the lack of enthusiasm and awareness of narcotics dealer convicts to take part in coaching activities, the lack of qualified human resources in the field of coaching, facilities and infrastructure that do not yet support the implementation of coaching. Efforts to overcome internal obstacles include increasing the synergy of correctional officers and increasing the role of Correctional Guardians, establishing cooperation agreements/MoUs, maximizing the use of existing facilities and infrastructure to support coaching activities. External constraints, namely the dense activity of partners during the commemoration of religious holidays so that the implementation of coaching is less than optimal. Efforts to overcome external obstacles are to improve communication with partners and continue to collaborate in the context of development, improvement and or expansion.